Interference Potential of FSS and BWA on the Extended C-Band - Lydia Sari; V. Windha Mahyastuty (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
The Indonesian government has allocated the 3.3-3.4 GHz band, which is adjacent to the extended C-band 3.4-3.7 GHz, for Broadband Wireless Access (BWA) services. The country has been using the extended C-band for Fixed Satellite Service (FSS). This research shows the interference potential between the two systems if an adjacent band is allocated for them. Using a clutter loss of 10 dB and site shielding of 40 dB, a BWA network consisting of 57 base-stations will potentially intefere an FSS with probability 56.16% if the protection distance used is 1.55 km. The interference potential will decrease to 0% if the protection distance is increased to 3 km. With a BWA network consisting of 20 base-stations, the interference probability is 10.72% and 0% for a protection distance of 1.55 km and 2 km, respectively.  With this interference potential it is urgent that Indonesia enforces interference mitigation techniques to protect FSS from disruptive interference.